2021
DOI: 10.1111/coa.13879
|View full text |Cite
|
Sign up to set email alerts
|

Use of an autoinflation device does not lead to a clinically meaningful change in hearing thresholds in children with otitis media with effusion

Abstract: Otitis media with effusion (OME) is characterised by fluid collection in the middle ear in the absence of acute infection. Conductive hearing loss is the main symptom and may be persistent or recurrent. 1 Spontaneous resolution is common; however, recovery is unpredictable and some children may experience a significant impact on their speech perception, language development, educational outcomes, behavioural development and quality of life. [2][3][4][5][6] A period of watchful waiting is the usual course of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…An open randomized study demonstrated moderate improvement among children with OME aged 4–11 years after insufflation therapy [ 6 ]. On the other hand, recently published results on the insufflation method were ambiguous [ 7 ]. Although a few clinical trials provided evidence for the efficiency of AMSA in OME, they included small and highly selective groups, which excluded adults [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…An open randomized study demonstrated moderate improvement among children with OME aged 4–11 years after insufflation therapy [ 6 ]. On the other hand, recently published results on the insufflation method were ambiguous [ 7 ]. Although a few clinical trials provided evidence for the efficiency of AMSA in OME, they included small and highly selective groups, which excluded adults [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%